(untitled) (Philological Studies, 2025)
In this paper, we address the numerous identities that we encounter in the character of King Marko. We focus on his religious identity through the folklore and literary works of the Macedonian authors Blazhe Koneski, Slobodan Mickovikj, Trajko Kitanchev, Slavcho Koviloski